Structural and Compositional Analysis of CZTSSe Thin Films by Varying S/(S+Se) Ratio - Mohamed Yassine Zaki; Florinel Sava; Iosif Daniel Simandan; Claudia Mihai; Alin Velea (Energies, 2024)
The development of kesterite (Cu2ZnSn(S,Se)4, CZTSSe) thin films for photovoltaic applications is highly necessary, given their composition of Earth-abundant, environmentally friendly elements and their compatibility with established photovoltaic technologies. This study presents a novel synthesis approach for CZTSSe films with varied S/(S+Se) ratios, ranging from 0.83 to 0.44, by a two-step magnetron sputtering deposition/annealing process. The first step consists in an initial deposition of stacked Mo/SnS2/Cu layers, which, upon thermal treatment in a sulfur atmosphere, were transformed into Cu2SnS3 (CTS) films. In the second step, further deposition of ZnSe and subsequent annealing in a tin and selenium atmosphere resulted in the formation of a CZTSSe phase. These processes were optimized to fabricate high-quality and single-phase CZTSSe films, thereby mitigating the formation of secondary phases. Characterization techniques, including scanning electron microscopy, demonstrated a clear correlation between decreased S/(S+Se) ratios and enhanced film densification and grain size. Moreover, grazing incidence X-ray diffraction and Raman spectroscopy confirmed a compositional and structural transition from close to CZTS to nearly a CZTSe phase as the S/(S+Se) ratios decreased. This study advances kesterite-based solar cell technology by enhancing the structural properties and crystallinity of the absorber layer, necessary for improving photovoltaic performance.